(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To compare the analgesic efficacy and adverse effects between the quadratus lumborum block combined with systemic analgesics and epidural analgesia following open colectomy. Subjects and methods: 60 patients were randomly divided into two groups: group M (n = 30) received a single-shot quadratus lumborum block combined with intravenous Paracetamol, Ketorolac, and Nefopam repeated every 8 hours for 72 hourspostoperatively; group C (n = 30) received epidural analgesia with Bupivacain e and Fentanyl. Results: Visual analog scale scores at rest and during movement within the first 24 hours showed no statistically significant differences between the two groups. After 24 hours, visual analog scale scores in group M were higher than those in group C, but still within an acceptable range. The additional Morphine consumption in groups M and C was 24.1 ± 10.2 mg and 19.1 ± 10.3 mg, respectively, with no statistically significant difference (p > 0.05). The incidence of nausea and vomiting was higher in group M (16.7% vs. 10%), while group C recorded additional adverse effects such as urinary retention and limb tremors. Conclusion: Quadratus lumborum block combined with Paracetamol, Ketorolac, and Nefopam is an effective and safe analgesic method, with potential to serve as an alternative to epidural analgesia following open colorectal surgery.